Toxic effects of boscalid on the growth, photosynthesis, antioxidant system and metabolism of Chlorella vulgaris. (November 2018) - Qian, Le; Qi, Suzhen; Cao, Fangjie; Zhang, Jie; Zhao, Feng; Li, Changping; Wang, Chengju
Abstract: Boscalid is one of the most frequently detected pesticides in main coastal estuaries in California, with concentrations as high as 36 μg/L. However, ecotoxicology information about boscalid to aquatic organisms is scarce. To investigate toxic effects and mechanisms of boscalid on freshwater algae Chlorella vulgaris ( C. vulgaris ), C. vulgaris were exposed to a range of boscalid concentrations (0, 0.8, 1.6, 2.4 and 3.2 mg/L) for 96 h to study the changes in photosynthetic pigment contents, responses of the antioxidant enzyme system and alterations in endogenous substances. Results indicated that the growth of algae and the content of chlorophyll and carotenoids were significantly inhibited by 1.6 mg/L boscalid. Reactive oxygen species (ROS) and oxidative damage of C. vulgaris could be induced by boscalid, in accordance with significant changes in ROS levels and a series of antioxidant enzyme activities. Moreover, the alterations in endogenous substances showed that boscalid could affect photosynthesis and energy metabolism of C. vulgaris . These results demonstrated that boscalid could induce impacts on C. vulgaris mainly through disturbing the photosynthesis, oxidative damage and energy metabolism. The present study provided a better understanding of the negative effects and mechanisms of bosaclid in microalgae. Graphical abstract: Image 1 Highlights: Boscalid inhibited the growth of C. vulgaris. Boscalid inhibited the synthesis of photosynthetic pigment. Boscalid induced oxidative damage of C. vulgaris. Boscalid resulted in alterations of endogenous substances in C. vulgaris. Boscalid may induce growth inhibition of C. vulgaris via disturbing the photosynthesis, oxidative stress and metabolism. Abstract : Boscalid may result in growth inhibition of C. vulgaris through disturbing the photosynthesis, oxidative stress and energy metabolism.